Smartphone application for Spastic ataxias cross-sectional validation of a newly developed smartphone app for remote monitoring in Spastic ataxias - Willemse, Ilse; Mellone, Sabato; Tacconi, Carlo; Ilg, Winfried; Schüle-Freyer, Rebecca; Synofzik, Matthis; Nonnekes, Jorik H.; van de Warrenburg, Bart P. C. (The cerebellum, 2025)
Effective trial-planning in Spastic ataxias (SPAX) is impeded by the absence of validated outcome measures for detecting longitudinal changes. Digital outcome measures show promise, demonstrating sensitivity to disease severity changes in ataxia and strong correlations with clinical scales. The objective of this study was to develop a smartphone application for SPAX (SPAX-app) to obtain valid digital outcome measures for use in clinical trials. The app contains four tasks assessing gait, standing balance (stance), and finger and hand movements. We carried out a validation study in 22 SPAX patients and 10 controls. Subjects performed the tasks three times during one visit. In parallel, we performed Ambulatory Parkinson's Disease Monitoring (APDM) sensor recordings, Q-motor upper limb assessment, and the Scale for the Assessment and Rating of Ataxia (SARA). Significant correlations were found between the SPAX-app and APDM or Q-motor for step time (r = 0.91), all measures of stance (r = 0.51-0.87) and duration of hand alternation (r = 0.64). No significant correlations were found for variability measures (e.g. standard deviation of step time). All tasks of the SPAX-app, except for stance, can discriminate SPAX from controls and show moderate to high test-retest reliability (ICC 0.67-0.97). Significant correlations were found between SARA and step time (r = 0.70), inter-onset interval in finger tapping (r = 0.57), and duration of hand alternation (r = 0.65). The stance task did not show significant correlations with SARA. With the SPAX-app, we present a set of digital outcome measures for potential use in clinical trials. Longitudinal studies are needed to evaluate whether these measures can track disease progression.
Gesehen am 25.02.2026